1999
DOI: 10.1161/01.hyp.33.6.1425
|View full text |Cite
|
Sign up to set email alerts
|

β-2 Adrenergic Receptor Variants Affect Resting Blood Pressure and Agonist-Induced Vasodilation in Young Adult Caucasians

Abstract: Abstract-Recent evidence suggests that the prodownregulatory Gly16 allele of the ␤-2 adrenergic receptor (␤-2 AR) is associated with essential hypertension in African Caribbeans. To further investigate the effect of the glycine (Gly)16 and arginine (Arg)16 ␤-2 AR variants on hemodynamics, we investigated the agonist-mediated in vivo vasodilation in normotensive Austrian Caucasians and analyzed the results with respect to the Gly16/Arg16 polymorphism. Fifty-seven normotensive men, 20 to 32 years of age with bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 29 publications
(24 reference statements)
6
96
1
2
Order By: Relevance
“…The findings demonstrate that the subjects carrying the Gly16 allele could have leptin resistance as well as blunted leptin-mediated plasma NE responses (sympathetic nerve activation). Further, the Gly16 allele has been described as a down-regulator of β2-adrenoceptor function (15,(38)(39)(40)(41). Thus, we could propose that a blunted β2-adrenoceptor function (15) and leptin resistance might be possible mechanisms in weight gain and BP elevation in obese subjects carrying the Gly16 allele of Arg16Gly, β2-adrenoceptor polymorphisms.…”
Section: Trp64argmentioning
confidence: 96%
“…The findings demonstrate that the subjects carrying the Gly16 allele could have leptin resistance as well as blunted leptin-mediated plasma NE responses (sympathetic nerve activation). Further, the Gly16 allele has been described as a down-regulator of β2-adrenoceptor function (15,(38)(39)(40)(41). Thus, we could propose that a blunted β2-adrenoceptor function (15) and leptin resistance might be possible mechanisms in weight gain and BP elevation in obese subjects carrying the Gly16 allele of Arg16Gly, β2-adrenoceptor polymorphisms.…”
Section: Trp64argmentioning
confidence: 96%
“…The β2AR polymorphisms accounted for ∼2% of the observed variation in blood pressure (Bray et al 2000). While results of some groups confirmed the association between the 16Gly allele and blood pressure (Kotanko et al 1997;Rosmond et al 2000;Gratze et al 1999), others found opposite effects, i.e., an association between the 16Arg allele and hypertension (Busjahn et al 2000;Bengtsson et al 2001a,b;Timmermann et al 1998) or no effects at all (Herrmann et al 2002;Kato et al 2001;Xie et al 2000; for a recent meta-analysis see Hahntow et al 2006). Again, differing inclusion of haplotypes, variations in ethnicities and different study designs may contribute to these sobering results.…”
Section: Genetic Variants In β-Adrenoceptor Genesmentioning
confidence: 98%
“…Specifically, studies have shown that b 1 -AR genotype is a significant predictor of blood pressure and ejection fraction responses to b-blockers, [4][5][6][7][8] and responses to b 2 agonists have been associated with b 2 -AR polymorphisms. 9,10 Dobutamine is a potent synthetic intravenous inotrope that is principally an agonist at b 1 -AR with mild stimulatory effects at b 2 -AR and a 1 -AR. A recent study in healthy volunteers pretreated with atropine showed that b 1 -AR codon 389 genotype was associated with greater contractile and systolic blood pressure (SBP) response to dobutamine.…”
Section: Introductionmentioning
confidence: 99%